Perbandingan Kemampuan Mastikasi Perempuan Menopause dan Pascamenopause Pengguna Gigi Tiruan Lengkap - Shanty Chairani (Maranatha Christian University, 2020)
Mastication is a complex process that aims to process the food into a bolus, which help in the absorption process of nutrients into the body. Loss of estrogen in menopausal condition causes decreased of bone density, muscle activity, salivary flow rate, and tooth loss that affect the ability of mastication. Wearing complete dentures can improve the masticatory ability. The aim of the present study was to compare the masticatory ability in menopausal and postmenopausal women complete denture wearers. Method: Observational analytic study with cross sectional design was conducted on 30 female subjects complete denture wearers at RSKGM, South Sumatra. Subjects consisted of two groups that were menopause group and postmenopausal women. Masticatory ability was measured using the chewing gum method with color-changeable chewing gum. Each subject was instructed to chew 1 piece of gum for 100 stroke. Color changes in chewing gum were visually measured and categorize into good and poor masticatory ability. Data were analyzed by Chi-square test. The results showed the menopausal women complete denture wearers group had better mastication ability (100%) than the postmenopausal women complete denture wearers group (26.7%). There was a significant difference in masticatory ability between the groups (p<0.05). In conclusion, masticatory ability of menopausal women complete denture wearer is better than postmenopausal women complete denture wearer. Keywords: Color-changeable chewing gum, complete dentures, mastication ability, menopause, postmenopause